(untitled) (Journal of Food and Dietetics Research, 2025)
Background and Aim: Women are the powerhouse of every household, filling many duties within the family. Lack of time and workload at workplace and home might have an impact on their health. They won’t give proper attention to their diet and health. Therefore, present study was taken to assess the body mass index status of professional women working in educational sectors in Indore city. Body Mass Index (BMI) is considered as a major determinant of health. Materials and Methods: A random sample of 500 women working in different schools and colleges of Indore city were chosen at age group between 30 - 45 years and comparison was done between these two groups. It is assumed that both study groups may have different job demands, resulting in various dietary choices. This can affect health status particu larly in relation to obesity in women. Obesity, thyroid, diabetes, hypertension, and hormonal disorders were also identi fied as frequent concerns among Indore women. To collect data from the respondents, a self-administered questionnaire was created. Results: According to the findings of this study, the health condition of school teachers and college teachers differed substantially in terms of BMI. A BMI comparison revealed that college teachers were more overweight as com pare to school teachers. Conclusion: Conclusion were drawn healthier BMI, active lifestyle and better dietary habits were witnessed in school teachers as compared to college teachers.